2020
DOI: 10.14531/ss2020.2.15-22
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and delivery in patients with idiopathic scoliosis

Abstract: Objective. To analyze the course of pregnancy and delivery that occurred before and after surgical correction of idiopathic scoliosis with  instrumented fixation of the spine.Material and Methods. The paper presents a retrospective randomized study of 100 patients of reproductive age (18–35 years) with Lenke type 2–6 idiopathic scoliosis. The following aspects of pregnancy were analyzed: the possibility of independent conception, the pain severity according to VAS during each of the three trimesters of pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…, managed conservatively (brace) or surgically). 11 , 12 , 17 , 25 , 35 , 38 , 43 , 44 , 58 In conservatively managed patients, Aulisa et al 15 reported no significant differences in the number of pregnancies in braced participants regardless of the size of the curve which was also reported by Cochrane and Nachemson 21 who found a pregnancy rate similar to the country’s national norm (Sweden). Conversely, compared to a healthy population, Misterska et al 32 reported a significant difference regarding the rate of pregnancy and the mean number of children.…”
Section: Evidence Synthesismentioning
confidence: 68%
See 4 more Smart Citations
“…, managed conservatively (brace) or surgically). 11 , 12 , 17 , 25 , 35 , 38 , 43 , 44 , 58 In conservatively managed patients, Aulisa et al 15 reported no significant differences in the number of pregnancies in braced participants regardless of the size of the curve which was also reported by Cochrane and Nachemson 21 who found a pregnancy rate similar to the country’s national norm (Sweden). Conversely, compared to a healthy population, Misterska et al 32 reported a significant difference regarding the rate of pregnancy and the mean number of children.…”
Section: Evidence Synthesismentioning
confidence: 68%
“… 10 , 55 - 59 Most were North American (40%) 6 , 10 , 12 , 16 , 17 , 19 , 22 , 23 , 25 , 26 , 35 , 38 , 41 , 42 , 45 , 46 , 49 , 52 , 55 , 57 or European (44%) studies. 11 , 14 , 15 , 20 , 21 , 24 , 28 - 34 , 37 , 44 , 47 , 50 , 51 , 53 , 56 , 58 , 59 The study population of all included publications was recruited from hospitals or medical centres, except for two studies, where participants were recruited from the Gothenburg Scoliosis Database. 20 , 21 …”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations